Kamza and Tirana: A Travel Captured in Correspondence. The Planned, the Unplanned, and Everything in Between - Pllumbi, Dorina; Vogel, Willie (Writingplace, 2023)
The text offers a glimpse into the conversation between two of the three organizers behind the training school titled ‘The Planned, the Unplanned, and Everything in Between’ held in Tirana and Kamza in March 2023. Three months before the training school, the two correspondents, Willie, visiting Albania for the first time through an STSM, and Dorina, temporarily located in the Netherlands, exchange daily thoughts aiming to interpret the two cities’ urban situations and sociopolitical conditions. Albania’s historical position at the edge of Europe has seen a remarkable shift in recent times, turning into an emerging discovery. Simultaneously, a burgeoning self-awareness of subverting narratives of representation has begun to take root among the Albanian youth – a phenomenon that adds depth and complexity to the ongoing dialogue. The transformation of the cities and the country is explained as multivocal while acknowledging protests, loss and destruction as part of a glorified urban project.